Remote monitoring with cardiac implantable electronic device to follow up pharmacodynamic effects of sacubitril/valsartan treatment: A case report - Uğur Önsel Türk; Emin Alioğlu (KARE Publishing, 2019)
Cardiac implantable electronic devices include remote monitoring tools intended to guide heart failure management. These tools allow for observation of some physiological functions, such as intrathoracic impedance (ITI), patient activity (PA), and heart rate variability (HRV). Sacubitril/valsartan is recommended in the current guidelines as foundational therapy for patients with heart failure and reduced ejection fraction. However, the effects of sacubitril/valsartan treatment on these physiological parameters remain unclear. To the best of our knowledge, this is the first case objectively documenting improvements in ITI, PA, and HRV values with sacubitril/valsartan treatment.